A novel zero knowledge proof of retrievability. (18th December 2019) - Yang, Dexin; Liu, Liming
Proof of retrievability is a cryptographic tool which interacts between the data user and the server, and the server proves to the data user the integrity of data which he will download. It is a crucial problem in outsourcing storage such as cloud computing. In this paper, a novel scheme called the zero knowledge proof of retrievability is proposed, which combines proof of retrievability and zero knowledge proof. It has lower computation and communication complexity and higher security than the previous schemes.